2017
DOI: 10.1074/jbc.m117.784678
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of H2S in vivo using the newly developed mitochondria-targeted mass spectrometry probe MitoA

Abstract: Hydrogen sulfide (H2S) is produced endogenously in vivo and has multiple effects on signaling pathways and cell function. Mitochondria can be both an H2S source and sink, and many of the biological effects of H2S relate to its interactions with mitochondria. However, the significance of mitochondrial H2S is uncertain, in part due to the difficulty of assessing changes in its concentration in vivo. Although a number of fluorescent H2S probes have been developed these are best suited to cells in culture and cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…1 C ; habitat × H 2 S: P < 0.001 in SI Appendix , Table S5 ), likely helping fish from sulfidic habitats to maintain H 2 S homeostasis during environmental exposure. To test this prediction in vivo, we used a novel mitochondria-specific H 2 S-probe (MitoA) that allows for the monitoring of relative H 2 S levels inside the mitochondria of living organisms ( 16 ). We measured mitochondrial H 2 S concentrations in this manner using laboratory-reared fish that were exposed to varying levels of environmental H 2 S. Because laboratory-reared fish were not available for the population pair from Pich, only two population pairs were used for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1 C ; habitat × H 2 S: P < 0.001 in SI Appendix , Table S5 ), likely helping fish from sulfidic habitats to maintain H 2 S homeostasis during environmental exposure. To test this prediction in vivo, we used a novel mitochondria-specific H 2 S-probe (MitoA) that allows for the monitoring of relative H 2 S levels inside the mitochondria of living organisms ( 16 ). We measured mitochondrial H 2 S concentrations in this manner using laboratory-reared fish that were exposed to varying levels of environmental H 2 S. Because laboratory-reared fish were not available for the population pair from Pich, only two population pairs were used for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it will also be interesting to investigate precisely how H 2 S production varies in different tissues and in different cellular locations following DR. These approaches may be made more feasible with the advent of novel chemical probes to determine H 2 S in vivo (Arndt et al 2017;Lau et al 2019). However, irrespective of these caveats, we have shown that endogenous H 2 S levels and associated signalling pathways differ significantly depending on genetic background in mice under both AL and DR conditions.…”
Section: Got1mentioning
confidence: 86%
“…This hypothesis has been supported by numerous observations in a variety of vertebrates that have shown; (1) hypoxia and H 2 S produce identical responses in a wide variety of physiological systems, (2) compounds that stimulate or inhibit H 2 S production often stimulate or inhibit hypoxic responses, (3) failure of H 2 S oxidation occurs at physiologically relevant P o 2 thereby increasing tissue H 2 S concentration and (4) O 2 ‐sensitive H 2 S metabolism occurs in the mitochondria (reviewed in). Furthermore, hypoxia has recently been shown to increase H 2 S concentration in mitochondria of myocardial cells furthering the case for mitochondrially mediated H 2 S production in O 2 sensing.…”
Section: Introductionmentioning
confidence: 92%